A study of rate, indications and maternal morbidity associated with cesarean delivery in a tertiary care hospital - Nigar, Asma; Ahmad, Ausaf; Khan, Khashia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cesarean section is one of the most commonly performed surgical procedures in obstetrics worldwide. Over the last three decades, a tremendous increase in cesarean section rates has been observed globally, which is a cause for concern as procedure is associated with higher morbidity and mortality compared to vaginal delivery. This study was done to analyze the rate and indications for cesarean section and associated maternal morbidity and mortality. Methods: This retrospective study was conducted over a period of 6 months from 1st October 2017 to 31st March 2018 in the department of Obstetrics and Gynecology, Integral Institute of Medical Sciences and Research, Lucknow, India. Data of patients who were admitted for delivery in department of Obstetrics and Gynecology in OPD or emergency were recorded. Statistical analysis of various parameters namely, the cesarean section rates, its indications, the patient’s morbidity and mortality was done. Results: The total numbers of women delivered over the study period were 577, out of which 210 patients underwent cesarean sections. The overall cesarean section rate in our study was 36.39%. Previous cesarean section was the leading indication of cesarean section (31.9%) followed by arrest of labor (18.1%), CPD (14.2%), and fetal distress (12.9%). Breech presentation (5.2%), failed induction of labor (4.8%), pregnancy induced hypertension (PIH) (3.8%), oligohydramnios (3.3%), obstructed labor (2.4%), APH (1.4%), multiple pregnancy and BOH accounted for 0.95% of cesarean sections. 9% patients had few complications mainly minor wound infection (2.4%) and postpartum hemorrhage (2%). There was no mortality during this period. Conclusions: Previous cesarean section has been found to be the main indication for cesarean section. So primary cesarean section should be reduced to decrease the overall cesarean rates. A comprehensive, evidence based approach needs to be introduced to monitor indication of all cesarean section.